Scalable Fabrication of Quasi-One-Dimensional van der Waals Ta2Pt3Se8 Nanowire Thin Films via Solution Processing for NO2 Gas Sensing over Large Areas - Choi, Kyung Hwan; Lee, Sang Hoon; Kang, Jinsu; Zhang, Xiaojie; Jeon, Jiho; Bang, Hyeon Suk; Kim, Yeongjin; Kim, Dahoon; Kim, Kyung In; Kim, Yeong Hyeop; Oh, Hyung Suk; Chang, Jongwha; et al. (ACS Applied Materials and Interfaces, 2024)
Solution-based processing of van der Waals (vdW) one- (1D) and two-dimensional (2D) materials is an effective strategy to obtain high-quality molecular chains or atomic sheets in a large area with scalability. In this work, quasi-1D vdW Ta2Pt3Se8 was exfoliated via liquid phase exfoliation (LPE) to produce a stably dispersed Ta2Pt3Se8 nanowire solution. In order to screen the optimal exfoliation solvent, nine different solvents were employed with different total surface tensions and polar/dispersive (P/D) component (P/D) ratios. The LPE behavior of Ta2Pt3Se8 was elucidated by matching the P/D ratios between Ta2Pt3Se8 and the applied solvent, resulting in N-methyl-2-pyrrolidone (NMP) as an optimal solvent owing to the well-matched total surface tension and P/D ratio. Subsequently, Ta2Pt3Se8 nanowire thin films are manufactured via vacuum filtration using a Ta2Pt3Se8/NMP dispersion. Then, gas sensing devices are fabricated onto the Ta2Pt3Se8 nanowire thin films, and gas sensing property toward NO2 is evaluated at various thin-film thicknesses. A 50 nm thick Ta2Pt3Se8 thin-film device exhibited a percent response of 25.9% at room temperature and 32.4% at 100 °C, respectively. In addition, the device showed complete recovery within 14.1 min at room temperature and 3.5 min at 100 °C, respectively.
Keywords: 1d van der waal; Gas-sensors; Liquid Phase; Liquid phase exfoliation; Liquid phasis; N-methyl-2-pyrrolidone; Quasi-one dimensional; Solution-processing; Thin-films; Van der Waal; 1D van der waals; dispersion; gas sensor; liquid phase exfoliation; solution processing; thin-film